Surgical treatment of intramedullary spinal cord ependymomas - Can outcome be predicted by tumor parameters? - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2004)
Objective: The aim of this study was to investigate whether the tumor parameters of spinal intramedullary ependymomas are significant predictors of clinical presentation and postsurgical outcome. Methods: The study involved 21 cases of intramedullary ependymoma that were operated on between 1988 and 2001. The patients were 13 mates (62%) and 8 females (38%), with an age range of 9-70 years (median 38 years). Results: in most cases (13; 62%), preoperative neurologic examination revealed a sensorimotor deficit in at least one limb. Complete tumor removal was achieved in all cases. The patients with wider tumors had poorer preoperative neurologic condition and poorer neurologic outcome. Tumor length (equivalent to myelotomy length) was not correlated with preoperative neurologic status, but longer length was significantly associated with development of dysesthesia post surgery. In contrast to tumor length, tumor/cord ratio (ratio of the tumor width to the largest cord width at the tumor site) was identified as a significant predictor of preoperative neurologic status and outcome. Ratio values of >0.80 were correlated with poorer preoperative clinical status and poorer neurologic outcome. Neither extent of edema (determined from length [in millimeters] of hyperintensity on T2-weighted images) nor presence of a cyst in the tumor was significant relative to postoperative neurologic recovery in these cases. Conclusions: This study demonstrated that the width of the tumor relative to the cord is the main predictor of neurologic presentation and postoperative status. The length of the tumor affects the postoperative dysesthesia development.
Keywords: dysesthesia; ependymoma; intramedullary; spinal; RESECTION